Surgical Intervention for Mediastinal Pancreatic Pseudocysts. A Case Series and Review of the Literature - Metaxa, Dafni; Balakrishnan, Anita; Upponi, Sara; Huguet, Emmanuel L; Praseedom, Raaj K (JOP. Journal of the Pancreas, 2015)
Context Development of mediastinal pancreatic pseudocysts is a rare complication of pancreatitis. There is currently no consensus on the optimal management of this condition, options for which include conservative management with somatostatin analogues, endoscopic drainage procedures and surgery. Case report Here we present two patients with mediastinal pancreatic pseudocysts which were initially managed endoscopically. However, in both cases, this led to complications secondary to the endoscopic procedures, recurrence or non-resolution of symptoms, requiring surgical cystogastrostomy and/or cystojejunostomy. Conclusion These cases suggest that surgery may be ultimately necessary for mediastinal pancreatic pseudocysts where endoscopic procedures might have a high likelihood of failure. Image: A well-defined rim enhancing pseudocyst.